2002
DOI: 10.1016/s0092-8674(02)00824-3
|View full text |Cite
|
Sign up to set email alerts
|

salvador Promotes Both Cell Cycle Exit and Apoptosis in Drosophila and Is Mutated in Human Cancer Cell Lines

Abstract: The number of cells in an organism is determined by regulating both cell proliferation and cell death. Relatively few mechanisms have been identified that can modulate both of these processes. In a screen for Drosophila mutations that result in tissue overgrowth, we identified salvador (sav), a gene that promotes both cell cycle exit and cell death. Elevated Cyclin E and DIAP1 levels are found in mutant cells, resulting in delayed cell cycle exit and impaired apoptosis. Salvador contains two WW domains and bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
732
5
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 777 publications
(779 citation statements)
references
References 28 publications
23
732
5
6
Order By: Relevance
“…Lats2 is also found mutated in human mesothelioma cell lines and non-small cell lung cancer (Strazisar et al, 2009;Murakami et al, 2011). Additionally, Sav1 and Mob1 mutations have been observed in human cancer cell lines and skin melanomas, respectively (Tapon et al, 2002;Lai et al, 2005). Together, these studies highlight a significant role of the Hippo pathway in organ size regulation and tumorigenesis.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 75%
See 2 more Smart Citations
“…Lats2 is also found mutated in human mesothelioma cell lines and non-small cell lung cancer (Strazisar et al, 2009;Murakami et al, 2011). Additionally, Sav1 and Mob1 mutations have been observed in human cancer cell lines and skin melanomas, respectively (Tapon et al, 2002;Lai et al, 2005). Together, these studies highlight a significant role of the Hippo pathway in organ size regulation and tumorigenesis.…”
Section: The Mammalian Hippo Pathwaymentioning
confidence: 75%
“…Extensive research has led to the identification of the Hippo tumor suppressor pathway as a key regulator of organ size in Drosophila and mammals (Pan, 2010). By genetic mosaic screens, mutation of the first batch of Hippo pathway genes warts (wts) (Justice et al, 1995;Xu et al, 1995), hippo (hpo) (Harvey et al, 2003;Jia et al, 2003;Pantalacci et al, 2003;Udan et al, 2003;Wu et al, 2003), and salvador (sav) (Kango-Singh et al, 2002;Tapon et al, 2002) were found to dramatically promote tissue overgrowth and organ size enlargement. These genes belong to the hyperplastic group of Drosophila tumor suppressors wherein mutations of these genes result in robust tissue overgrowth without alterations of cell fate determination or cell polarity (Hariharan and Bilder, 2006).…”
Section: The Drosophila Hippo Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…In budding and fission yeast, the scaffolding proteins Nud1p and Cdc11p/Sid4p support MEN and SIN signalling, respectively [10,11,16]. In flies, the scaffolding protein Salvador (Sav; the fly counterpart of Nud1p and Cdc11p/Sid4p) functions as a central tumour suppressor in Hippo signalling [26,[55][56][57][58]70]. However, the involvement of Sav in mitotic processes is yet to be tested.…”
Section: Hippo Signalling In G2/m In Drosophila Melanogastermentioning
confidence: 99%
“…Mats binds Warts and stimulates its kinase activity (He et al, 2005;Lai et al, 2005). Sav interacts through its WW-domains with the PPXY motif of Warts and functions as a scaffold to form the tripartite complex of Hippo, Sav and Warts (Tapon et al, 2002;Harvey et al, 2003). These studies lead to the hypothesis that Hippo/Sav complex activates Warts/ Mats complex.…”
Section: Introductionmentioning
confidence: 99%